2007
DOI: 10.1007/s11524-007-9225-z
|View full text |Cite
|
Sign up to set email alerts
|

Social Network-Related Risk Factors for Bloodborne Virus Infections Among Injection Drug Users Receiving Syringes through Secondary Exchange

Abstract: Secondary syringe exchange (SSE) refers to the exchange of sterile syringes between injection drug users (IDUs). To date there has been limited examination of SSE in relation to the social networks of IDUs. This study aimed to identify characteristics of drug injecting networks associated with the receipt of syringes through SSE. Active IDUs were recruited from syringe exchange and methadone treatment programs in Montreal, Canada, between April 2004 and January 2005. Information on each participant and on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Secondary exchange occurs most frequently within established injecting networks comprised of close friends, sexual partners and family members (Brothers, 2016; Bryant and Hopwood, 2009; Craine et al, 2010; De et al, 2008; Fisher et al, 2013; Green et al, 2010; Huo et al, 2005; Lenton et al, 2006; Lorvick et al, 2006; Marshall et al, 2015; Murphy et al, 2004; Newland et al, 2016; Snead et al, 2003; Tyndall et al, 2002) but it may also involve PWID who acquire large numbers of syringes to sell or distribute outside their personal networks often at some distance from a fixed-site SEP (Lenton et al, 2006; Newland et al, 2016; Valente et al, 1998; Valente et al, 2001). In Baltimore, for example, it was estimated such high-volume “satellite” exchangers, representing less than 10% of SEP clients, accounted for nearly 65% of syringes distributed (Valente et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary exchange occurs most frequently within established injecting networks comprised of close friends, sexual partners and family members (Brothers, 2016; Bryant and Hopwood, 2009; Craine et al, 2010; De et al, 2008; Fisher et al, 2013; Green et al, 2010; Huo et al, 2005; Lenton et al, 2006; Lorvick et al, 2006; Marshall et al, 2015; Murphy et al, 2004; Newland et al, 2016; Snead et al, 2003; Tyndall et al, 2002) but it may also involve PWID who acquire large numbers of syringes to sell or distribute outside their personal networks often at some distance from a fixed-site SEP (Lenton et al, 2006; Newland et al, 2016; Valente et al, 1998; Valente et al, 2001). In Baltimore, for example, it was estimated such high-volume “satellite” exchangers, representing less than 10% of SEP clients, accounted for nearly 65% of syringes distributed (Valente et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although the "street" availability of prescription analgesic opioids such as hydromorphone and morphine has increased in recent years, 7,8 intravenous use of heroin prevails in Vancouver and Montreal. 5,[9][10][11] Injectors are exposed to life-threatening health risks such as drug overdoses, bloodborne viral infections, endocarditis, and others. [12][13][14] Those who remain untreated or who are outside the social and health care system are known to experience higher rates of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The most common transmission route in Western countries remains injecting drug use, with an estimated 60%‐80% of the HCV‐positive population having acquired the virus via injecting risk behaviour . A variety of psychosocial factors have been associated with injecting risk behaviour: injecting frequency, poly‐drug use, having a sexual partner who also injects, trust and risk perception to name a few . Despite the continued injecting risks carried out by people who inject drugs, many studies have shown that fears of non‐adherence and low sustained virological response (SVR) rates are unjustified, with people who inject drugs (PWID) showing both successful adherence and high SVR rates …”
Section: Introductionmentioning
confidence: 99%